Investigation on pump as turbine (PAT) technical aspects for micro hydropower schemes: A state-of-the-art review. (November 2017) - Binama, Maxime; Su, Wen-Tao; Li, Xiao-Bin; Li, Feng-Chen; Wei, Xian-Zhu; An, Shi
Abstract: Energy is unarguably the key factor for today's economic and social development within nations. Electricity as one of many energy forms is a critical input to developing countries in the struggle to the national self-satisfaction in all domains. Rural electricity supply involved institutions have recently recommended the pump as turbine (PAT)-based micro hydropower plant (MHP) schemes for remote off-grid electrification, mostly from their economic advantages. However, from different published research findings, PAT-based MHP is not only simple and economically feasible, but has presented bottlenecks in the move to its full understanding. Moreover, compared to other clean energy technologies, PAT technology has not found much literature in academic published researches, thus contributing to its limited understanding within the community. Therefore, the PAT literature availability is one way to level up its understanding, which can be helpful to academic and professional communities. In the present study, a state-of-the-art review on the two most challenging PAT aspects, namely PAT performance prediction and PAT flow stability aspects are presented. In the presented literature, the selected energy sources history leading to the actual MHP global adoption was first briefly explained, followed by an intensive literature on PAT operations, where details about PAT selection and performance prediction were provided. Finally, the PAT flow stability aspects where pump-turbine S-shape and Saddle-type characteristics constitute the main focus, were discussed. It is worth an attention to mention that the words "pump-turbine", "Pump as turbine", and "reversible pump turbine"; are equally used throughout the whole literature. It is within the authors wish that this paper can scale up the reader's PAT technology understanding, thus serving awareness in the same.